Is Power Production Flexibility a Substitute for Storability? Evidence from Electricity Futures Prices - Mehtap Kilic; Ronald Huisman (Tinbergen Institute, 2010)
Electricity is not storable. As a consequence, electricity demand and supply need to be in balance at any moment in time as a shortage in production volume cannot be compensated with supply from inventories. However, if the installed power supply capacity is very flexible, variation in demand can be counterbalanced with flexible adjustment of production volumes. Therefore, supply flexibility can replace the role of inventory. In this paper, we question whether power production flexibility is a substitute for storability. To do so, we examine power futures prices from countries that differ in their power supply and test whether power futures prices contain information about expected future spot prices and risk premiums and examine whether futures prices from a market in which power supply is more flexible would lead to futures prices that are more in line with the theory of storage. We find the opposite; futures prices from markets with flexible power supply behave according to the expectations theory. The implicit view from futures prices is that flexibility is not a substitute for storability.
Keywords: G13; 330; Electricity futures prices; forward risk premium; theory of storage; expectations theory; Elektrizität; Strompreis; Risikoprämie; Erwartungstheorie